Improving risk management at highlands to increase corporate performance - Lê, Ngọc Oanh ([s.l.], 2020)
The ongoing development of F & B chains has attracted more and more domestic and foreign investors. So the war for the market in the chain in this industry is becoming more intense than ever. So in order to be successful in this area, companies have to overcome a lot of holy trials and risks, including the change in consumer behavior, effective employee management, competition with companies. It is true that only few companies can overcome these challenges, such as Trung Nguyen, Cong coffee, Highlands coffee because they know the tastes of Vietnamese people, provide quality products and services. For customers, they also know how to highlight the company in the market is fierce competition